A biophysically-defined hyaluronic acid-based compound accelerates migration and stimulates the production of keratinocyte-derived neuromodulators. Issue 1 (1st January 2019) - La Gatta, Annalisa; D'Agostino, Antonella; Schiraldi, Chiara; Colella, Giuseppe; Cirillo, Nicola
ABSTRACT: Hyaluronic acid (HA) preparations are widely used in clinical practice and recent data suggest that commercially available HA-based compounds promote ulcer re-epithelialization and induce pain relief. However, the pathophysiological basis of these effects remains poorly understood. In the present study, we investigated the biophysical, biomolecular and functional properties of a HA preparation combined with a pool of collagen precursor synthetic aminoacids, namely l-proline, l-leucine, l-lysine and glycine (Aminogam®). Hydrodynamic characterization of Aminogam® by size exclusion chromatography-triple detector array (SEC-TDA) revealed an average molecular weight in the range of 700–1700 kDa. Rheological measurements of the 1700kDa Mw lot showed a pseoudoplastic behaviour with a zero-shear viscosity (η0 ) equal to 90 ± 9 Pa∙s at 25°C and 55 ± 6 Pa∙s at 37°C. Automated time-lapse videomicroscopy studies in a fibroblast-free system demonstrated that 1% (v/v) Aminogam® significantly reduced the healing time of wounded keratinocyte monolayers. In AKGOS assays, Aminogam® stimulated cellular locomotion (chemokinesis) and directional migration (chemotaxis) of keratinocytes. Analysis of microarray data suggested that keratinocytes had a functional neuroendocrine machinery, and this was confirmed by testing the secretion of six neuroactive molecules by ELISA, namely α-MSH, β-endorphins, melatonin, substance P, cortisol, and neurotensin. Interestingly, Aminogam® regulated the production of several neuropeptides, including β-endorphins. In conclusion, our data shed light on the epithelial-dependent mechanisms that underlie the efficacy of Aminogam®, particularly in reference to wound healing and nociception.